2020
DOI: 10.1016/j.omtn.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Amido-Bridged Nucleic Acid-Modified Antisense Oligonucleotides Targeting SYT13 to Treat Peritoneal Metastasis of Gastric Cancer

Abstract: Patients with peritoneal metastasis of gastric cancer have dismal prognosis, mainly because of inefficient systemic delivery of drugs to peritoneal tumors. We aimed to develop an intraperitoneal treatment strategy using amido-bridged nucleic acid (AmNA)-modified antisense oligonucleotides (ASOs) targeting synaptotagmin XIII ( SYT13 ) and to identify the function of SYT13 in gastric cancer cells. We screened 71 candidate oligonucleotide sequences according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 43 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Patients with peritoneal metastasis of gastric cancer exhibit dismal survival outcomes 24 . In our cohort, ADAR1 up-regulation displayed a significant correlation to depth of invasion, TNM stage as well as peritoneal metastasis, as previously reported 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with peritoneal metastasis of gastric cancer exhibit dismal survival outcomes 24 . In our cohort, ADAR1 up-regulation displayed a significant correlation to depth of invasion, TNM stage as well as peritoneal metastasis, as previously reported 14 .…”
Section: Discussionmentioning
confidence: 99%
“…As the Syt13-VF mRNA utilizes the Syt13 UTR, it might be possible to use the fusion protein as a sensor to study Syt13 miRNA or antisense oligonucleotide function in silencing Syt13. This is important when aiming to target Syt13 for therapeutic purposes as it has been previously reported [27]. Finally, this novel tool will aid in monitoring Syt13-expressing cells under physiological and pathological conditions in vivo.…”
Section: Pancreatic Endocrine But Not Exocrine Cells Specifically Express Syt13 Proteinmentioning
confidence: 79%
“…In lung adenocarcinoma, SYT13 contributes to cellular proliferation, clonality, and anti-apoptotic effects [11], and in colorectal cancer, silencing SYT13 inhibits tumor growth in mouse models [10]. Our group previously found that intraperitoneal injection of SYT13 siRNA inhibited the peritoneal dissemination of gastric cancer in mouse models, and that SYT13 expression was an independent risk factor for peritoneal recurrence in patients with gastric cancer [9,14]. Despite these previous findings, the significance of SYT13 in BC remains unclear.…”
Section: Discussionmentioning
confidence: 99%